Socialization on Social Media Addiction and Mental Health among Christian Youth - Habel Saud; Yansen Alberth Reba (LP4MK STKIP PGRI Lubuklinggau, 2025)
This community service program aims to provide socialization and mentoring for Christian youth of the I.S. Kijne Congregation in Abepura, Papua, to address social media addiction through a community-based digital wellness intervention program. The program integrates evidence-based psychological approaches with Christian theological perspectives to enhance mental health and the quality of interpersonal relationships. The one-day intensive socialization activity was designed using a Community-Based Participatory Education approach combined with Experiential Learning Theory. The program incorporates Cognitive Behavioral Therapy techniques, digital detox strategies, and Christian stewardship principles. The effectiveness assessment utilized the Bergen Social Media Addiction Scale and mental health indicators among 45 participants aged 16–25 years. The preliminary survey revealed an alarming condition: 84.4% of respondents used social media for more than four hours per day, with 31.1% at high risk and 13.3% experiencing addiction. A strong correlation was found between problematic social media use and depression (r=0.567, p<0.001) as well as anxiety (r=0.523, p<0.001). The program results showed a significant increase in knowledge (≥40% pre–post improvement), a decrease in Fear of Missing Out (≥30%), and behavioral commitment (80% of participants pledged to reduce usage). The culturally adapted and faith-integrated program model proved effective for promoting digital wellness within religious communities. The program’s success demonstrates the importance of combining scientific evidence with theological frameworks to create sustainable behavioral change through peer support systems and community integration. This model offers a replicable solution for addressing digital addiction in faith-based contexts.